A path-planning algorithm for soccer robots based on repeated modification of Bezier polynomials - Pedrasa, Michael Angelo A. (2003)
The objective of an attacking robot in robot soccer is to kick the ball towards a specified direction, with or without the presence of stationary or moving obstacles. A path-planner controls the motion of the robot. This thesis implements a path-planner that is based on repeated modification of bezier polynomials. The proposed algorithm steers the robot by: (a) selecting the control points that would define the bezier curve, (b) determining the parametric equation from the control points, (c) computing the curvature from the parametric equation and (d) computing the wheel velocities so the robot would move along an arc with equal curvature. The proposed algorithm is compared to the uni-vector field and line-circle algorithms. These algorithms are already used in robot soccer competitions. The algorithms executed 17 test cases, where each test case is described by the placement of the robot, ball and obstacles. The objective of the robot is to kick the ball towards a specific direction. The performances of the algorithms are compared by comparing the success rate, kicking accuracy and frequency of collisions. The results verified the validity of the proposed algorithm. It showed that the performance of the proposed algorithm is comparable to the performance of the line-circle and uni-vector algorithm.